BHLHE40 Regulates IL-10 and IFN-γ Production in T Cells but Does Not Interfere With Human Type 1 Regulatory T Cell Differentiation - Uyeda, Molly Javier; Freeborn, Robert A.; Cieniewicz, Brandon; Romano, Rosa; Chen, Ping (Pauline); Liu, Jeffrey Mao-Hwa; Thomas, Benjamin; Lee, Esmond; Cepika, Alma-Martina; Bacchetta, Rosa; Roncarolo, Maria Grazia (Frontiers in Immunology, 2021)
Type 1 regulatory T (Tr1) cells are subset of peripherally induced antigen-specific regulatory T cells. IL-10 signaling has been shown to be indispensable for polarization and function of Tr1 cells. However, the transcriptional machinery underlying human Tr1 cell differentiation and function is not yet elucidated. To this end, we performed RNA sequencing on ex vivo human CD49b+LAG3+ Tr1 cells. We identified the transcription factor, BHLHE40, to be highly expressed in Tr1 cells. Even though Tr1 cells characteristically produce high levels of IL-10, we found that BHLHE40 represses IL-10 and increases IFN-γ secretion in naïve CD4+ T cells. Through CRISPR/Cas9-mediated knockout, we determined that IL10 significantly increased in the sgBHLHE40-edited cells and BHLHE40 is dispensable for naïve CD4+ T cells to differentiate into Tr1 cells in vitro. Interestingly, BHLHE40 overexpression induces the surface expression of CD49b and LAG3, co-expressed surface molecules attributed to Tr1 cells, but promotes IFN-γ production. Our findings uncover a novel mechanism whereby BHLHE40 acts as a regulator of IL-10 and IFN-γ in human CD4+ T cells.